A Practical verification of a computer simulation for injection molding applied to amorphous thermoplastic polyesters - F. H. Axtell (2018)
A comparison has been made between the pressure drops arising during injection molding as predicted by a simulation software package named SIMPOL®and as measured during molding trials conducted to study the effects of molding variables. The theory used to design the software has been reviewed and the operation described. The comparison was made using amorphous thermoplastic polyesters, PET and PCTG. The molding conditions used for the simulated trials were the same as those used in practical molding trials. The molding trials were conducted using a mold fitted with a cavity transducer and a machine fitted with a hydraulic pressure sensor. The simulation shows qualitative agreement to the observations made in practice. The difference in pressure drop values are attributed to the software’s dependence on crystalline PET physical properties for calculations and an overestimation of the frozen layer thickness by the simulation model. Overall the simulation has been shown to be a pragmatic tool for the production engineer working in the thermoplastic injection molding industry. © 1991, Taylor & Francis Group, LLC. All rights reserved.